Synthesis of actinide chlorides for molten salt preparation - P Chevreux; S Serp; M Duchateau (The Australasian Institute of Mining and Metallurgy, 2024)
Molten salt reactor (MSR) is a promising advanced reactor system aiming to the transmutation of minor actinides such as americium in order to reduce the inventory of ultimate nuclear waste. The fuel is a molten salt in which actinides are homogeneously dissolved in the liquid phase. A chloride salt may be retained for this concept, as it provides low melting point, high solubility of actinides, harder neutron spectrum. To avoid corrosion and precipitation issues, molten salt composition has to be carefully controlled with impurity content as low as possible. Obtaining pure actinide chlorides without contaminants such as oxide, oxychloride, hydroxide and water is still a challenge. To prepare actinide-bearing salt, the chlorination of actinides oxides was investigated in an unstirred reactor under flowing gas as solid-gas reaction. The carbochlorination of PuO2 were performed in the temperature range of 600 to 800°C with chlorine gas as a chlorinating agent and the presence of solid carbon. PuCl3 was successfully synthesised by this method and characterised by X-ray diffraction measurements but some impurities such as oxide phase remain inside the formed product. Refinements of anhydrous and hydrated PuCl3 phases by Le Bail method were also performed for crystalline materials definition. Conversion mainly depends on the chlorinating temperature and the contact between the oxide and the chlorinating agent. A conversion value of 70–80 per cent was achieved at 700°C from PuO2 with quite high specific surface area. The conversion rate was not improved with increasing the chlorination time. The volatilisation of Pu was observed during the carbochlorination experiments. To avoid a loss of Pu caused by sublimation, the chlorination temperature should be limited to 650°C despite that the conversion of PuO2 to PuCl3 was enhanced by increasing temperature. Both carbochlorination and hydrochlorination of AmO2 were also carried out leading to the formation of AmCl3. These first results suggest that americium oxide was chlorinated more readily than plutonium oxide. The purity of produced PuCl3 and AmCl3 still deserves further investigations.